Quaternary Writing Skills of Class XI Students of SMA Negeri 6 Pekanbaru for the 2022/2023 Academic Year - Nindya Pradana Nurhidayah; Mangatur Sinaga; Silvia Permatasari (JETISH: Journal of Education Technology Information Social Sciences and Health, 2023)
This study describes and analyzes the ability of grade XI students at SMA Negeri 6 Pekanbaru in writing quatrains. This research is a quantitative research because the data presented in this study is in the form of numbers. Data analysis techniques in this study use descriptive statistical techniques. The research instrument used in this study was a quaternary type poetry writing test based on the form of writing one stanza consisting of only four lines. In the test instrument used, researchers provide several themes and students are welcome to write quatrains based on one of the selected themes. Students are asked to make quatrains by paying attention to existing assessment aspects, namely the suitability of themes, diction, rhyme, language style and mandates. The formulation of the problem in this study is what is the level of quaternary writing ability of grade XI students of SMA Negeri 6 Pekanbaru for the 2022/2023 academic year? Based on the results of the study, the quaternary writing ability of grade XI students of SMA Negeri 6 Pekanbaru for the 2022/2023 academic year is classified as moderate. This is known after testing using a one-sample t test with an average of 75.43.